Awareness and Appreciation of Advertising Language - Trisnowati Tanto (Universitas Sanata Dharma, 2019)
This research focuses on advertising language in advertisement slogans of various products written in English. The grand theory used is Stylistics, which is the study of the style of language or the study of the use of distinctive linguistic expressions and how they affect the target audience. To limit the discussion, this research more specifically covered the use of rhetorical figures and doublespeak in advertising language. These language features basically have the same functions, namely the aesthetic and persuasive functions, which aim to attract the audiences attention. This research, using an explanatory research method, was done to find out peoples awareness and appreciation of the outstanding use of advertising language by distributing questionnaires with Likert scale to the students and alumni of the English Department of a private university in Indonesia. Considering that in an advertisement there is also the visual aspect besides the textual aspect, the research was also done to find out whether or not there is a strong correlation between peoples awareness and appreciation of the visual and textual aspects.Keywords: advertising language, awareness, appreciation